Age‐related alterations in muscle architecture are a signature of sarcopenia: the ultrasound sarcopenia index. Issue 4 (1st June 2021) - Narici, Marco; McPhee, Jamie; Conte, Maria; Franchi, Martino V.; Mitchell, Kyle; Tagliaferri, Sara; Monti, Elena; Marcolin, Giuseppe; Atherton, Philip J.; Smith, Kenneth; Phillips, Bethan; Lund, Jonathan; et al.
Abstract: Background: The assessment of muscle mass is a key determinant of the diagnosis of sarcopenia. We introduce for the first time an ultrasound imaging method for diagnosing sarcopenia based on changes in muscle geometric proportions. Methods: Vastus lateralis muscle fascicle length (Lf) and thickness (Tm) were measured at 35% distal femur length by ultrasonography in a population of 279 individuals classified as moderately active elderly (MAE), sedentary elderly (SE) ( n = 109), mobility impaired elderly (MIE) ( n = 43), and in adult young controls (YC) ( n = 60). The ratio of Lf/Tm was calculated to obtain an ultrasound index of the loss of muscle mass associated with sarcopenia (USI). In a subsample of elderly male individuals ( n = 76) in which corresponding DXA measurements were available (MAE, n = 52 and SE, n = 24), DXA‐derived skeletal muscle index (SMI, appendicular limb mass/height 2 ) was compared with corresponding USI values. Results: For both young and older participants, USI values were found to be independent of sex, height and body mass. USI values were 3.70 ± 0.52 for YC, 4.50 ± 0.72 for the MAE, 5.05 ± 1.11 for the SE and 6.31 ± 1.38 for the MIE, all significantly different between each other ( P < 0.0001). Based on the USI Z ‐scores, with reference to the YC population, the 219 elderly participants were stratified according to their muscle sarcopenic status. Individuals with USI values within a range of 3.70 < USI ≥ 4.23 were classified as non‐sarcopenic (prevalence 23.7%), those with USI values within 4.23 < USI ≥ 4.76 were classified as pre‐sarcopenic (prevalence 23.7%), those with USI values within 4.76 < USI ≥ 5.29 were classified as moderately sarcopenic (prevalence 15.1%), those with USI values within range 5.29 < USI ≥ 5.82 were classified as sarcopenic (prevalence 27.9%), and those with USI values >5.82 were classified as severely sarcopenic (prevalence 9.6%). The DXA‐derived SMI was found to be significantly correlated with USI ( r = 0.61, P < 0.0001). Notably, the USI cut‐off value for moderate sarcopenia (4.76 a.u.) was found to coincide with the DXA cut‐off value of sarcopenia (7.26 kg/m 2 ). Conclusions: We propose a novel, practical, and inexpensive imaging marker of the loss of muscle mass associated with sarcopenia, called the ultrasound sarcopenic index (USI), based on changes in muscle geometric proportions. These changes provide a useful 'signature of sarcopenia' and allow the stratification of individuals according to the presence and severity of muscle sarcopenia. We are convinced that the USI will be a useful clinical tool for confirming the diagnosis of sarcopenia, of which the assessment of muscle mass is a key‐component.